Allergens and allergenicity in cell-cultured meat: Current status and reflections - Yun Li; Fen Jin; Yongzhong Qian; Shouwei Wang; Shijie Ding; Yingying Li; Lei Hu; Runrun He; Yuru Yan; Tianyi Tao; Meijuan Bo (Trends in Food Science & Technology, 2026)

Establishment of DAS-ELISA and lateral flow immunochromatography for the detection of peanut allergen Ara h 3 after heat-moisture treatment - Shuo Yang; Fuyu Sun; Xiao Wu; Pengbo Huang; Jinglong Qu; Runrun He; Yuanyuan Cui; Jun Xi (Food Chemistry, 2025)

Circulating Level of Blood Iron and Copper Associated with Inflammation and Disease Activity of Rheumatoid Arthritis - Huijuan Wang; Runrun Zhang; Jie Shen; Yehua Jin; Cen Chang; Mengjie Hong; Shicheng Guo; Dongyi He (Biological Trace Element Research, 2023)
This study aims to compare the concentrations of circulating levels of iron, zinc, and copper in blood samples of rheumatoid arthritis (RA) patients which determine the correlations with inflammation and disease activity. A total of 102 RA patients and 66 healthy controls were enrolled. Circulation of iron, zinc, and copper levels in whole blood were assessed. Hemoglobin, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), anticyclic citrullinated peptide antibody (anti-CCP) levels were collected. A meta-analysis was performed to validate our findings. Single and multiple variate generalized linear regression were applied to identify the correlation between trace elements and clinical characteristics. Blood copper level was significantly higher in RA patients ( P < 0.001), while iron and zinc levels were decreased ( P < 0.001 and P = 0.02, respectively). Meta-analysis confirmed our findings for zinc (SMD = − 1.17, P < 0.001) and copper (SMD = 1.24, P < 0.001). Copper level was positively correlated with DAS28-CRP ( r = 0.35, P < 0.01), CRP ( r = 0.45, P < 0.01) and ESR ( r = 0.58, P < 0.01). Iron level was negatively correlated with DAS28-CRP ( r = − 0.37, P < 0.01), CRP ( r = − 0.46, P < 0.01) and ESR ( r = − 0.55, P < 0.01). Circulating blood copper was significantly higher and positively correlated with DAS28-CRP and inflammatory markers, while circulating blood iron was decreased and negatively correlated with DAS28-CRP and inflammatory markers in RA patients.

Selection and validation of reliable reference genes in Gossypium raimondii - Runrun Sun; Qiuling He; Baohong Zhang; Qinglian Wang (Biotechnology Letters, 2015)